The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jth.14943
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function and bleeding in chronic lymphocytic leukemia and mantle cell lymphoma patients on ibrutinib

Abstract: Background: Therapy with irreversible Bruton's tyrosine kinase inhibitor ibrutinib in chronic lymphocytic leukemia (CLL) and mantle cell lymphoma (MCL) is associated with bleeding. Objectives: To propose the predictive markers of such bleeding, as well as mechanisms responsible for decreased bleeding at later therapy stages. Patients/Methods: We investigate platelet functional activity in 50 CLL and 16 MCL patients on ibrutinib using flow cytometry and light transmission aggregometry. Results: Prior to treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The highest risk of haemorrhage occurs in the first months of treatment, suggesting that both disease and treatment-related factors influence the severity of this AE (Ysebaert et al, 2014;Lipsky et al, 2015;Brown et al, 2019;Dmitrieva et al, 2020). Furthermore, patients with B-cell malignancies have an intrinsic risk of bleeding (Gifkins et al, 2015).…”
Section: Increased Risk For Bleedings Under Btki Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest risk of haemorrhage occurs in the first months of treatment, suggesting that both disease and treatment-related factors influence the severity of this AE (Ysebaert et al, 2014;Lipsky et al, 2015;Brown et al, 2019;Dmitrieva et al, 2020). Furthermore, patients with B-cell malignancies have an intrinsic risk of bleeding (Gifkins et al, 2015).…”
Section: Increased Risk For Bleedings Under Btki Treatmentmentioning
confidence: 99%
“…Low-grade bleeding events are usually not associated with thrombocytopenia, suggesting an impaired platelet function as the cause of the AE as reviewed (Berglöf et al, 2015). However, Dmitrieva et al (2020) investigated the platelet function in 50 CLL and 16 MCL patients and their results suggest that ibrutinibdependent bleeding in CLL patients requires a setting of three mechanisms. Most important was a decreased platelet count prior ibrutinib treatment.…”
Section: Increased Risk For Bleedings Under Btki Treatmentmentioning
confidence: 99%
“…83,84 Ibrutinib treatment further reduced procoagulant platelet formation upon strong stimulation, which was already reduced in patients with chronic lymphocytic leukemia which could also contribute to the development of bleeding. 85 On the other hand, recent study suggests that procoagulant platelets are upregulated by desmopressin and may play a role in its mechanism of action of desmopressin. 86 Another study 87 showed the ability of procoagulant platelets to bind factor VIIa and promote factor X activation by it, which may be a mechanism of action of recombinant-activated factor VII.…”
Section: Generation Of Procoagulant Platelets In Patientsmentioning
confidence: 99%
“…Consideration of bleeding risk is therefore increasingly needed in oncological practice. In this edition of the journal, Dmitrieva and colleagues explore the timing of bleeding risk and platelet dysfunction in lymphoproliferative disorders treated with the first‐in‐class Bruton's tyrosine kinase (BTK) inhibitor ibrutinib 3 …”
Section: Figurementioning
confidence: 99%
“…Dmitrieva and colleagues examined platelet dysfunction over time during ibrutinib treatment 3 . They found that platelet function decreased following initiation of ibrutinib, but then improved in concert with disease response.…”
Section: Figurementioning
confidence: 99%